Modulation transfer function in optical and electro-optical systems - Boreman, G. D. (Tutorial texts in optical engineering ;, 2001)
This tutorial introduces the theory and applications of MTF, used to specify the image quality achieved by an imaging system. It covers basic linear systems theory and the relationship between impulse response, resolution, MTF, OTF, PTF, and CTF. Practical measurement and testing issues are discussed.